Analisis Perbandingan Rasio Keuangan Perusahaan Sektor Telekomunikasi Yang Terdaftar Di Bei Periode 2020 – 2022 - Ananta Kumala Sari; Sullicyanna Luna Bianca; Ari Rohmana; Devira Larasati; Cholis Hidayati (Jurnal Akuntan Publik, 2024)
This study aims to analyze the comparison of financial ratios in the telecommunications sector listed on the Indonesia Stock Exchange for the period 2020-2022. Financial ratios are financial analysis tools used to evaluate company performance by comparing financial data contained in financial statements. Liquidity ratios, profitability ratios, activity ratios, solvency ratios, and market ratios are types of ratios. This research uses a qualitative method with secondary data on financial statements in the telecommunications sector for the 2020-2022 period. The data can be obtained by visiting the official website of the Indonesia Stock Exchange or visiting the company's website. The samples used were only four companies, namely PT Smartfren Telecom Tbk (FREN), PT Indosat Tbk (ISAT), PT XL Axiata Tbk (EXCL), and PT Telekomunikasi Indonesia Tbk (TLKM) using purposive sampling technique. The results of this study indicate that of the four companies, the ratio of PT Telekomunikasi Indonesia Tbk is superior compared to the other three companies because the company can utilize its cash and assets well, fulfill its obligations both short and long term, manage the company well and efficiently, and generate high profits with a reasonable share price.